Modification and Innovation of Flour-Based Products into Contemporary Pancong Cakes under the MBKM Program of Indo Global Mandiri University Students - Letari, Rahayu Tri; Hertati, Lesi; Asharie, Asmawati (International Journal of Social Science and Community Service, 2023)
Pancong Cake is a traditional cake originating from Betawi, and the name "Pancong" is derived from the Betawi language. It holds a distinct identity as a traditional Betawi cake. Over time, the Pancong Cake, once only adorned with granulated sugar, now boasts a variety of toppings to stay current with contemporary tastes. Kekinian Pancong Cake is a food establishment with a booth concept that integrates with other modified and innovated traditional food stands. Situated in the Kambang Iwak area of Palembang, South Sumatra, Pancong Kekinian Cake addresses a community service activity. This initiative presents a two-fold solution. The first solution imparts knowledge to Pancong Cake proprietors on how to create a product with the ability to capture a large market through outreach. The second solution provides examples of product strategies as reference material, presented in a relaxed discussion format while enjoying Pancong Cake. The proposed solution involves fostering collaboration between two or more third-party brands (co-branding) to enhance the product image. This, in turn, aims to bolster consumer confidence, potentially resulting in increased profits or added value to products or services resulting from the co-branding. The outcomes of this community service activity will be disseminated in an accredited national journal article. It is hoped that the concept of this activity can be implemented more broadly by Pancong Cake owners to boost sales through effective product strategies.